Konsep Mengasihi Berdasarkan Injil Yohanes 13:34-35 Dan Penerapannya Bagi Orang Percaya - Vivian Hia; Pensensius Emen (Sekolah Tinggi Teologi Sriwijaya, 2023)
The command to love one another is a command given by Jesus, He wants everyone who follows Him to live in love. Jesus commanded His disciples to practice love so that they can be reflectors of the light of love wherever they are. Someone who lives in God's love will have love for others, love that is accompanied by concrete actions. The purpose of this study is for believers to understand that the love they share or express to others is not only an act of social life, but also an authentic demonstration of the love that comes from Christ Jesus. The method used in this study is a qualitative research method that uses the four-layer exegesis method of biblical meaning. The four layers consist of the first layer (Historia/Sarkic), the second layer, (Theoria/Noetic/spiritual meaning), the third layer (Psychic/moral), and the fourth layer (Anagogic/Escatology). Thus, through the principle of excavation, it shows the result that loving one's neighbor is the lifestyle of every follower of Christ.